Direct evidence for distinct colour origins in ROY polymorphs. Issue 38 (2nd September 2021) - Warren, Lisette R.; McGowan, Evana; Renton, Margaret; Morrison, Carole A.; Funnell, Nicholas P.
Abstract : Alternative colour origins in ROY polymorphs are conclusively determined for the first time, using high-pressure diffraction and hybrid DFT. Abstract : ROY is one of the most well-studied families of crystal structures owing to it being the most polymorphic organic material on record. The various red, orange, and yellow colours of its crystal structures are widely-believed to originate from molecular conformation, though the orange needle (ON) polymorph is thought to be an exception. We report high-pressure, single-crystal X-ray measurements which provide direct experimental evidence that the colour origin in ON is intermolecular, revealing that the molecule undergoes minimal deformation but still exhibits a pronounced, reversible, pale orange → dark red colour change between ambient pressure and 4.18 GPa. Our experimental data are rationalised with band structures, calculated using an accurate hybrid DFT approach, where we are able to account for the variation in colour for five polymorphs of ROY. We highlight the outlier behaviour of ON which shows marked π⋯π stacking interactions that are directly modified through application of pressure. Band structure calculations confirm these intermolecular interactions as the origin of the colour change.